The needs of families of patients admitted into the intensive care unit in third world countries: an integrative literature review - Ngema, Nomthandazo (My University, 2021)
Background: The sudden admission of a patient with life-threatening illness into the intensive care unit has a profound effect on the family members of patients. While the needs of familiesof patients admitted in the intensive care unit have been examined from various perspectives, the needs of patient’s families in third world countries are yet to be explored through this review. This will be unique to the body of knowledge Aim: The aim of this review was to gather evidence related to the needs of families of patients admitted in the intensive care unit in third world countries. Methods: An integrative literature review methodology was used. The review was guided by the five stages outlined by Whittemore and Knafl. Literature search was conducted using databases: SCOPUS, PubMed, CINAHL, MEDLINE and Psycho INFO. Keywords used included: family, needs, intensive care unit, and third world countries. A total of 492 studies were retrieved after using the search filters and date limits. Ten articles were finally included as they met the inclusion criteria set for the review. Results: Ten studies were included in this review. The need domains were synthesised under five themes: ‘assurance’; ‘information’; proximity’; ‘comfort’ and ‘support’. Conclusion: In third-world countries, family members of critically ill patients in the ICU perceive and share similar needs just as those in the first and second world countries, especially in the domains of assurance and information. Family members form an integral part of patient care in the ICU. The multidisciplinary team need to recognise the needs of family members and develop supportive structures to attend to their needs. Paying attention to these needs will enhance effective communication.
A research report submitted in fulfilment of the requirements for the degree Master of Science in Nursing to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2021